2021
DOI: 10.1016/j.heliyon.2021.e07883
|View full text |Cite
|
Sign up to set email alerts
|

On the pulsating (m,c)-Fibonacci sequence

Abstract: In this paper, we study new ideas in the generalization of additive and multiplicative pulsating Fibonacci sequences. Then, we construct two types of pulsating Fibonacci sequences of the m th order. Moreover, the closed forms of the two sequences are derived by basic linear algebra.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…As shown in Figure A, the following genes were enriched in clusters: Gnas , Gprasp1 , Krt7 , Gcp4 , Esyt1 , Krt15 , Diras2 , Celf4 , Cp ; these may be the genes related to Tipe1 that regulate β cell function. The roles of Gnas , Gprasp1 , Krt7 , and Gcp4 have been reported in glycolipid metabolism, [ 41–44 ] among which Gnas plays a key role in regulating β cell function and has been listed as a candidate gene for T2D pathogenesis. [ 28,29,40 ] Krt7 is a constituent of the keratin network in mouse islets; however, Krt7 is not expressed in human pancreatic islets under basal conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure A, the following genes were enriched in clusters: Gnas , Gprasp1 , Krt7 , Gcp4 , Esyt1 , Krt15 , Diras2 , Celf4 , Cp ; these may be the genes related to Tipe1 that regulate β cell function. The roles of Gnas , Gprasp1 , Krt7 , and Gcp4 have been reported in glycolipid metabolism, [ 41–44 ] among which Gnas plays a key role in regulating β cell function and has been listed as a candidate gene for T2D pathogenesis. [ 28,29,40 ] Krt7 is a constituent of the keratin network in mouse islets; however, Krt7 is not expressed in human pancreatic islets under basal conditions.…”
Section: Resultsmentioning
confidence: 99%
“…[ 28,29,40 ] Krt7 is a constituent of the keratin network in mouse islets; however, Krt7 is not expressed in human pancreatic islets under basal conditions. [ 45 ] Gcp4 is located in the membrane, [ 44 ] indicating an indirect interaction and regulation between Tipe1 and Gcp4. We next determined the interaction of Tipe1 with Gαs (encoded by Gnas ) or GΑSP1 (encoded by Gprasp1 ) (Figure 3B; Figure S8A, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…The optimized lattice constants and related cell volume are presented in Table S6 (Supporting Information), which meet the calculation requirements. [ 67–69 ] The terminated surfaces of clean LiO and NbO 2 are cleaved in a vacuum slab with 20 Å thickness and a crystal thickness of 25 Å, as shown in Figure 7a‐IV,V, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…[ 70,71 ] This is supported by Parsaeimehr et al. [ 72 ] who discovered that small animals like invertebrates commonly consume toxins like microplastics, which they can absorb. The presence of microplastics in marine species is important for the estuarine food web since the study can serve as a baseline for these microplastics to go up the trophic chain.…”
Section: Heterogeneity On Abundance and Distribution Of Microplastic ...mentioning
confidence: 93%
“…Some studies found that these invertebrates tend to be selected as ideal test organisms since they can be easily found, simple to sample, stress-resistant, sessile animals and most crucially are popularly known as benthic filter feeder for microplastics. [70,71] This is supported by Parsaeimehr et al [72] who discovered that small animals like invertebrates commonly consume toxins like microplastics, which they can absorb. The presence of microplastics in marine species is important for the estuarine food web since the study can serve as a baseline for these microplastics to go up the trophic chain.…”
Section: Microplastic Ingested By Benthic Organism In Malaysiamentioning
confidence: 94%